Power-law low-temperature asymptotics for spatially nonhomogeneous s-wave superconductors - Gabovich, Alexander M.; Voitenko, Alexander I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
It is shown that low temperature asymptotics of various thermodynamic and transport properties of s-wave superconductors can become power-law ones if wide distributions of gap values exist, originating from structure domains, charge stripes, charge-density waves or other mesoscopic nonhomogeneities. The relevant experimental data for high-Tc oxides are analyzed on the basis of the developed theory.